HUBUNGAN PERSONAL HIGIENE DENGAN KEJADIAN SKABIES DI PONDOK PESANTREN DI KOTA SURAKARTA - , HENY SASMITA, Prof. Dr. dr. Soeyoko, DTM&H, SU ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Preliminary observation showed that there are students with scabies at Ta'mirulislam Boarding School of Surakarta Municipality. The disease may arise due to poor hygiene. Objective: To identify association between personal hygiene (habit and treatment of clothes) and the incidence of scabies at Ta'mirulislam Boarding School. Method: The study was analytic observational with cross sectional design. Population were all students at the boarding school, comprising as many as 275 students. Samples consisted of 96 students that were randomly taken with lottery system. Data were obtained through questionnaire and analyzed using univariate, bivariate with chi square statistical test and multivariate with logistic regression analysis. Results: Variable statistically had significant association with the incidence of scabies was personal hygiene that included habit of bathing, cleaning bedroom, sleeping together in one bed, sharing towels, washing hands, ironing clothes, changing clothes and washing towels. Conclusion: There was significant association between personal hygiene and the incidence of scabies.